PENERIMAAN KAS DALAM MENINGKATKAN PENGENDALIAN KEUANGAN INTERNAL PADA RUMAH SAKIT JIWA GRHASIA DAERAH ISTIMEWA YOGYAKARTA - Irine Diana Sari Wijayanti; Herman Wahyu dwi Maelana; Novita Sari (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
The type of research used is qualitative research. The subject of writing in this paper are 3 resource persons, while the object of research on cash receipts is the activity of Cash Receipts in Improving Internal Control at the RSJ. Grhasia Special Region of Yogyakarta. Data analysis in this study used flow model analysis techniques. The steps of data flow model analysis according to Miles and Huberman (2012:15-19). The result is cash receipts and transfers at the RSJ. Grhasia Daerah Istimewa Yogyakarta is in accordance with what is stated in the SOP for the finance section. Then regarding the elements of the internal control system of the financial section of cash receipts at the RSJ. Grhasia Daerah Istimewa Yogyakarta is good because cash receipts are deposited every day at the bank. Constraints on cash receipts at the RSJ. Grhasia Daerah Istimewa Yogyakarta, which is after 20.00 hours the cash receipt process is received at the pharmacy installation and psychologist consultation is not in accordance with the cash receipts procedure applicable in the SOP. Efforts to overcome obstacles in the cash receipts process after 20.00 hours are that the cashiers have submitted them to the pharmacy installation according to the cash receipts financial management mechanism and related to psychologist consultations there should be coordination between the information department, cashiers and psychologists, and the cashiers should have a CMS (Cast Management System). ) in order to see daily transactions via transfer.